Successful pregnancy outcomes in a patient with type A insulin resistance syndrome. Issue 6 (June 2015) - Enkhtuvshin, B.; Nagashima, S.; Saito, N.; Wakabayashi, T.; Ando, A.; Takahashi, M.; Sakai, K.; Yamamuro, D.; Nagasaka, S.; Tamemoto, H.; Ishibashi, S.
Abstract Background The management of severe insulin resistance during pregnancy is challenging because of the increased risk of perinatal complications for both mother and fetus. We describe two consecutive pregnancies in a patient with severe insulin resistance caused by a mutation in the β subunit of the insulin receptor. Case report A non‐obese Japanese woman was diagnosed as having diabetes mellitus during her first pregnancy at age 31 years. She presented at 6 weeks' gestation with a fasting plasma glucose concentration of 15.1 mmol/l and an HbA1c level of 95 mmol/mol (10.8%). Fasting insulin concentration was high at 68.8 μU/ml, suggesting severe insulin resistance. Anti‐insulin and insulin‐receptor antibodies were both negative. Genetic analysis revealed an in‐frame heterozygous deletion mutation (∆Leu999) in the insulin receptor gene. Despite large daily doses (up to 480 units per day) of insulin aspart and isophane, the patient's postprandial plasma glucose level exceeded 11.1 mmol/l. In the patient's second pregnancy, the addition of metformin at a dose of 2250 mg per day achieved tighter glycaemic control, with lower doses of insulin lispro and isophane (up to 174 units/day). Both newborns, who were found to carry the same mutation, were small for gestational age and developed transient hypoglycaemia after birth. Conclusion Adding metformin to the conventional insulin regimen effectively achieved tight glycaemic control with a lower dose of insulin. The mutation of the insulin receptor gene might underlie the intrauterine growth retardation of the newborns. To our knowledge, this is the first report of successful management of diabetes mellitus in a pregnant woman with type A insulin resistance syndrome.